¿LIBERTAD Y DIGNIDAD TRAS LA INDEPENDENCIA POLÍTICA? UN DEBATE SOBRE LAS TESIS POSCOLONIALES - Vela Orbegozo, Bernardo (Cultura Latinoamericana, 2021)
In the same way that the physical and moral devatation generated in the so-called words wars the European scenario that led to the emergence of critical thinking, the barbarism of colonialism, the atrocity of the wars of Independence and the internal struggles for power that followed. Those wars of Independence -in many cases to this day- were de American, African and Asian scene that led to the emergence of postcolonial critical thougt, the study of which is the object of this article.